Pt single atom / cyanide modified g-C3N4 material and its preparation and application in photocatalytic H2O2 production
By modifying Pt single atoms and cyano groups on the g-C3N4 material, a Pt single atom/cyano modified g-C3N4 material with high efficiency photocatalytic properties was solved, and the existing photocatalytic activity of unsatisfactory in H2O2 synthesis was achieved, and efficient and stable H2O2 synthesis was achieved.
Patent Information
- Application Number
- CN202411879904.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-19
AI Technical Summary
When catalyzing H2O2 synthesis, existing photocatalysts have problems such as poor catalytic activity, insufficient redox potential of water, low selectivity, and low apparent quantum yield and solar-chemical energy conversion efficiency.
The g-C3N4 material is modified by Pt single atom/cyano group, and the cyano modified g-C3N4 material is prepared by solvent heat treatment and calcination, and photoreduction is carried out under light to form a chemical bond between Pt particles in the single atomic state and the cyano group.
The efficiency of photocatalytic H2O2 is significantly improved, the yield of H2O2 can reach 43.67 mmol h-1 g-1, the apparent quantum efficiency (AQE) is 15.86%, and the photocatalytic performance of the material is stable.
Smart Images

Figure CN119318984B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic materials, and in particular to the field of H2O2 photocatalytic materials. Background Art
[0002] As one of the most important chemicals in the world, hydrogen peroxide (H2O2) is not only widely used in the fields of environment, chemical industry, and medicine, but also attracts close attention as a new type of solar fuel that is easy to store and transport. Therefore, the design and development of efficient, stable, cheap, and environmentally friendly H2O2 preparation technology has attracted great attention from scientific researchers around the world and is currently the research frontier in the field of energy and environment.
[0003] An ideal photocatalyst for the synthesis of H2O2 should have key features such as a wide absorption range, strong stability, high charge separation efficiency, and appropriate redox ability. Compared with other photocatalysts, g-C3N4 not only has a potential that spans the oxygen reduction reaction (ORR) and water oxidation reaction (WOR), but also its suitable band gap (about 2.7 eV) gives the material visible light response characteristics. However, g-C3N4 materials have problems such as low light energy utilization efficiency, fast carrier recombination rate, and low productivity caused by H2O2 decomposition. Therefore, its photocatalytic H2O2 synthesis efficiency is still difficult to meet actual needs. In order to fully tune the key steps of the H2O2 reaction, the literature (YAN SW, LI Y, YANG XY, et al. Photocatalytic H2O2 generationreaction with a benchmark rate at air-liquid-solid joint interfaces [J]. AdvMater, 2024, 36(9): 2307967) discloses the introduction of pyrrole units and cyano groups into the polymer g-C3N4 and its application in photocatalytic H2O2 synthesis. The study found that the material can promote the spatial separation of HOMO and LUMO orbitals, thereby improving the carrier separation efficiency. The H2O2 generation rate of the three-phase system in pure water conditions can reach 2063.21 μmol g -1 h -1. In addition, the literature (KOFUJI Y, OHKITA S, SHIRAISHI Y, et al. Graphitic Carbon Nitride Dopedwith Biphenyl Diimide: Efficient Photocatalyst for Hydrogen PeroxideProduction from Water and Molecular Oxygen by Sunlight [J]. ACS Catal, 2016,6(10): 7021-7029; SHIRAISHI Y, KANAZAWA S, KOFUJI Y, et al. Sunlight-DrivenHydrogen Peroxide Production from Water and Molecular Oxygen by Metal-FreePhotocatalysts [J]. Angew Chem Int Edit, 2014, 53(49): 13454-13459) disclosed that aromatic diimides, such as biphenylenediamine (BDI) and o-phenylenediamine (PDI), and other electron-withdrawing groups with high electron affinity can adjust the redox potential, shift the valence band level of the original g-C3N4 photocatalyst positively, promote the water oxidation process, and thus increase the photocatalytic H2O2 production.
[0004] Although existing research can improve the photocatalytic H2O2 production effect to a certain extent, current research work still faces problems such as insufficient water redox potential, low selectivity, and low apparent quantum yields (AQYs) and solar-to-chemical energy conversion (SCC) efficiency. Therefore, how to further improve the efficiency of photocatalytic H2O2 production remains a severe challenge facing the industrialization of this technology. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a Pt single atom / cyanide modified g-C3N4 material, aiming to prepare a catalyst with excellent photocatalytic H2O2 production performance.
[0006] The second purpose of the present invention is to provide Pt single atom / cyanide modified g-C3N4 material obtained by the preparation method.
[0007] The third object of the present invention is to provide an application of Pt single atom / cyanide modified g-C3N4 material in the photocatalytic preparation of H2O2.
[0008] The principle of photocatalytic preparation of H2O2 is to catalytically reduce the oxygen in the solution. Its principle and catalytic ideas are fundamentally different from conventional photocatalytic applications such as photocatalytic hydrogen production. Materials with good photocatalytic activity such as photocatalytic hydrogen production are not necessarily suitable for the application of photocatalytic production of H2O2. In view of the general problem of unsatisfactory catalytic activity in the photocatalytic preparation of H2O2, attempts have been made to use g-C3N4 materials with a certain H2O2 production capacity as a carrier, and to use it to load Pt active particles in the hope of obtaining superimposed composite advantages. However, it was discovered in the early stages of research and development that the inappropriate combination of the two made it difficult to effectively solve the physicochemical structure of Pt and the combination of the two, and it was difficult to obtain the expected composite effect. In response to this problem, the present invention has provided the following solutions after further in-depth research, specifically:
[0009] A method for preparing a Pt single atom / cyano modified g-C3N4 material, comprising subjecting a solution containing raw materials A and B to a solvent thermal treatment, followed by a roasting treatment, to obtain a cyano modified g-C3N4 material; then subjecting the cyano modified g-C3N4 material and a Pt source to liquid phase aging, freezing, and then photoreduction under a light intensity of 100 to 500 mW to obtain the Pt single atom / cyano modified g-C3N4 material;
[0010] The raw material A comprises at least one of Formula 1 and Formula 2;
[0011] Formula 1;
[0012] Formula 2;
[0013] The chemical formula of the raw material B is MCl, wherein M is at least one of Na and K.
[0014] In order to solve the problem that it is difficult for Pt and g-C3N4 to achieve the expected photocatalytic H2O2 production effect, the present invention innovatively performs solvent thermal treatment and roasting on raw materials A and B, so that cyano-modified g-C3N4 materials can be prepared, and further used as a substrate to participate in the photocatalytic reaction of Pt source, so that Pt can be unexpectedly induced to uniformly deposit on the g-C3N4 material and form a single atomic structure. In addition, the chemical anchoring mechanism can be used to target the cyano group of the g-C3N4 framework branch to avoid falling off and agglomeration, and fully expose the reaction active site. Studies have shown that the material prepared by the method of the present invention can unexpectedly significantly enhance the composite effect of Pt and g-C3N4, and can significantly optimize the effect of the prepared material in photocatalytic H2O2 production.
[0015] The present invention also shows that the combined control of the types and proportions of raw materials A and B as well as the solvent thermal conditions can help to further coordinate and prepare g-C3N4 materials that are more conducive to inducing targeted dispersion of Pt single atoms, which helps to further improve the photocatalytic H2O2 production effect of the prepared materials.
[0016] Preferably, the raw material A is a compound of formula 1. The present invention has shown that the use of formula 1 as raw material A, combined with the process of the present invention, can induce g-C3N4 materials with more suitable cyano-modified characteristics, which is expected to further induce the in-situ targeted single-atom distribution of Pt, which helps to further improve the photocatalytic H2O2 production effect of the prepared material.
[0017] Preferably, in the raw material B, M is Na. The present invention shows that the use of the raw material B, combined with the process of the present invention, is helpful to further regulate the cyano modification characteristics of the g-C3N4 material, to further induce the in-situ targeted single-atom distribution of Pt, and to further improve the photocatalytic H2O2 production effect of the prepared material.
[0018] Preferably, the weight ratio of the raw material A to the raw material B is 1:1-5; more preferably 1:1.5-2.5, and more preferably 1:2-2.5. The present invention shows that under the preferred conditions, it can be combined with other processes to further induce the in-situ targeted single-atom distribution of Pt, which helps to further improve the photocatalytic H2O2 production effect of the prepared material.
[0019] In the present invention, the solvent in the solution comprises water; wherein the concentration of raw material A can be 20-50 g / L.
[0020] In the present invention, the solvothermal temperature is 100-180 °C, more preferably 110-130 °C. Studies have shown that the preferred solvothermal temperature is conducive to further cyano modification of g-C3N4 materials, which is expected to further induce the in-situ targeted single-atom distribution of Pt, and help to further improve the photocatalytic H2O2 production effect of the prepared material.
[0021] In the present invention, the holding time at the solvent thermal temperature is 1 to 8 h. Considering the efficiency and effect, it can be further 2 to 5 h, and further can be 3 to 4 h.
[0022] In the present invention, the solvothermal system can be dried based on conventional means (such as rapidly freezing a mixture of the solvothermal system and a cooling medium such as dry ice or liquid nitrogen, followed by vacuum freeze drying), and then subjected to calcination treatment.
[0023] In the present invention, there is no particular requirement for the calcination atmosphere, and for example, it may be a protective atmosphere, and further may be at least one of nitrogen and an inert gas.
[0024] In the present invention, the calcination temperature is 450-650°C, further 500-600°C, and further 540-560°C. The preferred temperature can further optimize the physical and chemical structure of the cyano-modified g-C3N4 material, which helps to further optimize the subsequent single-atom targeted loading of Pt and the effect of producing H2O2.
[0025] In the present invention, the holding time at the roasting temperature is 2 to 8 hours, and can be further extended to 3 to 6 hours in consideration of the effect and efficiency.
[0026] In the present invention, the Pt source may be other water-soluble Pt-containing components such as chloroplatinic acid hexahydrate.
[0027] In the present invention, the Pt source is 10 wt%~50 wt% of the cyano-modified g-C3N4 material, more preferably 20 wt%~40 wt%, and further preferably 25 wt%~35 wt%. The present invention shows that based on the special cyano-modified g-C3N4 material, further combined with the combined control of the amount of Pt source, it is helpful to further improve the single-atom chemical targeted distribution of Pt, which helps to further enhance the photocatalytic H2O2 production effect of the prepared material.
[0028] In the present invention, the solvent for liquid phase aging is, for example, water, or a mixed solvent of water and a water-soluble organic solvent.
[0029] In the present invention, the temperature of liquid phase aging is 15-45°C.
[0030] In the present invention, the liquid phase deposition time may be more than 1 h, further may be 1 to 10 h, further may be 3 to 6 h.
[0031] In the present invention, the pH of the starting solution for controlling liquid phase aging is 5 to 10; further 6 to 9.5, further 7 to 9. The present invention shows that aging at the preferred pH helps to further facilitate the single-atom targeted synthesis of Pt and helps to further improve the effect of photocatalytic H2O2 production.
[0032] In the present invention, under the special cyano-modified g-C3N4 material and its induction mechanism, the combined control of the light intensity of photoreduction can further facilitate the uniform targeted induction of Pt and the formation of single-atom, stable Pt particles, thereby helping to further improve the photocatalytic H2O2 production effect of the prepared material.
[0033] In the present invention, the light intensity of photoreduction is 250-350 mW.
[0034] In the present invention, the photoreduction time is 2 to 15 minutes. Studies have shown that under the preferred light intensity and time, it is helpful to further optimize the targeted induction effect of the cyano-modified g-C3N4 material on the single atom Pt, and to improve the photocatalytic H2O2 production effect of the prepared material.
[0035] The present invention also provides the Pt single atom / cyanide modified g-C3N4 material obtained by the preparation method; it includes a cyanide modified g-C3N4 material and single-atom Pt particles dispersed on the surface thereof, and there is a chemical bonding reaction between the single-atom Pt particles and the cyanide material on the g-C3N4.
[0036] In the present invention, thanks to the control of the preparation method, the prepared material can be endowed with special physical and chemical characteristics, and the material with the characteristics can unexpectedly have unexpected catalytic advantages in photocatalytic H2O2 production.
[0037] The present invention also provides the application of the Pt single atom / cyano group modified g-C3N4 material prepared by the preparation method; the material is used as a catalyst for photocatalytic preparation of H2O2.
[0038] The present invention can be based on conventional ideas and means, and can use the Pt single atom / cyanide modified g-C3N4 material for photocatalytic preparation of H2O2.
[0039] Beneficial Effects
[0040] The present invention innovatively subjects raw materials A and B to solvent thermal treatment, thereby preparing cyanide-modified g-C3N4 material, which is further involved in the photocatalytic reaction of a platinum source. The electrons generated by the photoexcited g-C3N4 are transferred to the cyanide group, which can form physical and chemical reactions with Pt to assist its photoreduction. In this way, Pt can be unexpectedly induced to be anchored in a single-atom state on the g-C3N4 material, thereby obtaining a material with excellent photocatalytic H2O2 production.
[0041] The Pt single atom / cyanide modified g-C3N4 material of the present invention can reduce the carrier recombination efficiency, reduce the band gap value, and enhance the light absorption range. In addition, it also improves the separation and migration efficiency of carriers, and acts as a high-activity site to reduce the H2O2 synthesis barrier and synergistically improve the charge migration kinetics of carriers, thereby achieving high H2O2 synthesis efficiency. For example, the efficiency of the material of the present invention in the process of photocatalytic synthesis of H2O2 can reach 43.67 mmol h -1 g -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 1 and 2. The X-ray diffraction patterns of the g-C3N4 photocatalysts prepared in Example 1 and Comparative Examples 1, 2 and 3.
[0043] Figure 2 4. The Fourier transform infrared spectra of the g-C3N4 photocatalysts prepared in Example 1 and Comparative Examples 1, 2 and 3.
[0044] Figure 3 TEM images of the g-C3N4 photocatalysts prepared in Comparative Example 2 and Example 1, wherein (a) is a TEM image of the g-C3N4 photocatalyst prepared in Comparative Example 2, and (b) is a TEM image of the g-C3N4 photocatalyst prepared in Example 1.
[0045] Figure 4 2. The photoluminescence spectra of the g-C3N4 photocatalysts prepared in Example 1 and Comparative Examples 1, 2 and 3.
[0046] Figure 5 The ultraviolet-visible absorption spectra and Kubelka-Munk equation conversion diagrams of the g-C3N4 photocatalysts prepared in Example 1 and Comparative Examples 1, 2, and 3 are shown in FIG. 1 , wherein (a) is the ultraviolet-visible absorption spectrum of the g-C3N4 photocatalysts prepared in Example 1 and Comparative Examples 1, 2, and 3; (b) is the Kubelka-Munk equation conversion diagram of the g-C3N4 photocatalysts prepared in Example 1 and Comparative Examples 1, 2, and 3.
[0047] Figure 6 This is the H2O2 cycle performance of the g-C3N4 photocatalyst prepared in Example 1. DETAILED DESCRIPTION
[0048] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.
[0049] Example 1
[0050] Step 1: Disperse 4 g of formula 1 in water and ultrasonicate for 10 min (the concentration of formula 1 is 30-40 g / L), then add 8 g of sodium chloride powder, transfer to a reactor and solvothermally heat at 120 °C for 3 h, cool to room temperature and freeze in liquid nitrogen and freeze-vacuum dry, transfer the powder to a crucible and heat to 550 °C (calcination temperature) at a heating rate of 5 °C / min under a protective atmosphere (Ar), calcine for 4 h, then wash (water wash, ethanol wash) and dry to obtain cyano-modified g-C3N4 material.
[0051] Step 2:
[0052] 50 mg of dried cyano-modified g-C3N4 material powder was dispersed in water (the concentration of cyano-modified g-C3N4 material was 30-40 g / L), and then 30 wt% of the weight of cyano-modified g-C3N4 material was added with hexahydrate chloroplatinic acid, and 1 M NaOH was added to adjust its pH to 9. After stirring at room temperature for 5 h, it was frozen with liquid nitrogen and placed under simulated sunlight for 5 min, where the light intensity was 300 mW, to obtain Pt single atom / cyano-modified g-C3N4 material (catalyst). The XRD, FT-IR, and TEM of the prepared material are shown in Figure 2. Figure 1~Figure 3 . Figure 1 In the cyano-modified g-C3N4 material in step 1 and Example 1, the (002) diffraction peak shifts from 27.4° to 27.8° due to the introduction of cyano electron-withdrawing groups. Figure 2 The FT-IR is shown at 2177.7 cm -1 The vibration peak at the position indicates that the cyano group has successfully branched into the g-C3N4 molecular structure. Figure 3 (b) The uniformly dispersed Pt single atoms in the transmission electron microscope image provide highly active sites for the reaction. Photoluminescence spectrum, UV-visible absorption spectrum and Kubelka-Munk equation conversion diagram are shown in Figure 4~Figure 5 . H2O2 cycle performance see Figure 6 .
[0053] test:
[0054] 5 mg of the catalyst was dispersed in a mixed solution of 90 mL of ultrapure water and 10 mL of isopropanol, and then the solution was placed in an ultrasonic machine for 20 min. During the photocatalytic reaction, the solution was stirred and the reaction temperature was maintained at 25 °C. The H2O2 performance test was performed under a light source equipped with a >420 nm filter. 2 mL of the reaction solution was taken out every 10 min, and 1 mL of the supernatant was taken after centrifugation. 2 mL of potassium iodide solution (100 mM) and 50 μL of ammonium molybdate solution (100 mM) were added, and then the absorbance test was performed in the UV-visible absorption spectrum. The photocatalytic synthesis of H2O2 experimentally showed that the synergistic effect of Pt single atoms and cyano groups can maximize the photocatalytic H2O2 synthesis efficiency of g-C3N4, and the maximum H2O2 yield is 43.67 mmol h -1 g -1 The apparent quantum efficiency (AQE) is 15.86%, and its cycle performance is as follows Figure 6 The H2O2 production in the 4th hour was 87.32% of that in the first hour, indicating the performance stability of the material.
[0055] Example 2
[0056] Compared with Example 1, the only difference is that the conditions in step 1 are changed, and the experimental groups are:
[0057] Group A: The amount of sodium chloride was adjusted so that the weight ratio of Formula 1 to sodium chloride was changed to 1:1;
[0058] Group B: The amount of sodium chloride was adjusted so that the ratio of formula 1 to sodium chloride was 1:4;
[0059] Group C: Solvothermal temperature was 100 °C, time was 2 h. Calcination temperature was 500 °C, calcination time was 3 h.
[0060] Group D: Solvothermal temperature was 150 °C, time was 5 h. Calcination temperature was 600 °C, calcination time was 6 h;
[0061] Group E: Replace sodium chloride with an equal weight of potassium chloride;
[0062] Group F: Formula 2 is used to replace the formula 1 in equal amounts;
[0063] Other operations and parameters are the same as in Example 1.
[0064] The photocatalytic rates, AQE under 420 nm monochromatic light and Pt loading of Examples 1 and 2 are shown in Table 1:
[0065]
[0066] As shown in Table 1, it can be seen from Groups A and B of Example 1 and Example 2 that the ratio of raw materials A and B is controlled at 1:1~5, and good H2O2 production performance can be obtained, especially at a ratio of 1:1.5~2.5, better synergistic performance can be obtained. In addition, it can be seen from Groups C and D of Example 1 and Example 2 that better H2O2 production performance can be obtained when the solvent thermal temperature is 110~130°C and the calcination temperature is 540~560°C. In addition, it can be seen from Example 1 and Examples 2E and 2F that the use of Formula 1 and sodium chloride as raw materials is helpful for the joint synergy with subsequent processes, which helps to further improve the photocatalytic H2O2 production performance of the prepared material.
[0067] Example 3
[0068] Compared with Example 1, the only difference is that the conditions in step 2 are changed, and the experimental groups are:
[0069] Group A: The amount of chloroplatinic acid hexahydrate added was 10 wt% of the weight of the cyano-modified g-C3N4 material;
[0070] Group B: the addition amount of chloroplatinic acid hexahydrate was 50 wt% of the weight of the cyano-modified g-C3N4 material;
[0071] Group C: the pH of the solution was adjusted to 7 with 1 M NaOH;
[0072] Group D: The pH of the solution was adjusted to 5 with 1 M HNO3;
[0073] Group E: The solution was not regulated in pH, that is, pH 6.6;
[0074] Other operations and parameters are the same as those in Example 1. The photocatalytic rate, AQE under 420 nm monochromatic light and Pt loading of Example 3 are shown in Table 2:
[0075]
[0076] It can be seen from Table 2 that the addition amount of chloroplatinic acid hexahydrate is 10~50wt% of the weight of the cyano-modified g-C3N4 material, especially at a ratio of 20~40wt.%, which helps to better induce the targeted connection of Pt single atoms based on the cyano-modified g-C3N4 material, and helps to further improve its H2O2 production performance.
[0077] Example 4
[0078] Compared with Example 1, the only difference is that the conditions in step 2 are changed, and the experimental groups are:
[0079] Group A: light intensity was 100 mW, and illumination time was 3 minutes;
[0080] Group B: light intensity was 500 mW, and illumination time was 10 min;
[0081] Other operations and parameters are the same as in Example 1.
[0082] The photocatalytic rate, AQE under 420 nm monochromatic light and Pt loading of Example 4 are shown in Table 3:
[0083]
[0084] It can be seen from Table 3 that controlling the light intensity between 100 and 500 mW is helpful for substrate-induced single-atom chemical distribution of Pt. On this basis, controlling the light intensity between 250 and 350 mW is helpful for further synergistically improving the physicochemical structural characteristics and further enhancing the H2O2 production performance of the material.
[0085] Comparative Example 1
[0086] Compared with Example 1, the only difference is that sodium chloride is not added in step 1, step 2 is not performed, and the g-C3N4 material prepared in step 1 is directly used as a catalyst for producing H2O2. Other operations and parameters are the same as in Example 1.
[0087] Comparative Example 2
[0088] Compared with Example 1, the only difference is that sodium chloride is not added in step 1, and other operations and parameters are the same as in Example 1.
[0089] Comparative Example 3
[0090] Compared with Example 1, the only difference is that step 2 is not performed, and the cyano-modified g-C3N4 material obtained in step 1 is directly used as a catalyst for producing H2O2. Other operations and parameters are the same as those in Example 1.
[0091] Comparative Example 4
[0092] Compared with Example 1, the only difference is that the solvent thermal reaction in step 1 is changed to stirring at room temperature for 12 h, and the other operations and parameters are the same as in Example 1.
[0093] Comparative Example 5
[0094] Compared with Example 1, the only difference is that ammonium chloride is used to replace the sodium chloride in an equal amount, and other operations and parameters are the same as those in Example 1.
[0095] The photocatalytic rates, AQE under 420 nm monochromatic light and Pt loading of Comparative Examples 1 to 5 are shown in Table 4:
[0096]
[0097] Identification and analysis:
[0098] 1. Characterization of g-C3N4 photocatalyst synergistically regulated by Pt single atoms and cyanide groups:
[0099] X-ray diffraction spectrum: Figure 1 The (100) diffraction peak at 10° in Comparative Example 3 and Example 1 disappears, indicating that during the thermal polymerization process, the reaction of raw materials A and B reduces the long-range order within the structural plane. At the same time, the introduction of cyano electron-withdrawing groups causes the (002) diffraction peak of Comparative Example 3 and Example 1 to move from 27.4° to 27.8°, indicating that strong end groups can strengthen the interaction between adjacent g-C3N4 layers.
[0100] Fourier transform infrared spectroscopy: Figure 2 Center at 809 cm -1 The peak at 1200-1700 cm represents the stretching vibration of the triazine unit or the heptazine ring. -1 The peak at 3000~3600 cm belongs to aromatic CN or C=N heterocycle. -1 The peak of 2177.7 cm-1 belongs to the stretching vibration of NH bond. -1An additional peak appeared at , which is the characteristic peak of cyano group, proving that the NaCl template method successfully introduced cyano group into g-C3N4.
[0101] Transmission electron microscope image: Figure 3 It is the transmission electron microscope image of comparative example 2 and embodiment 1. Figure 2 It can be found that Pt is distributed on the surface of g-C3N4 in the form of nanoparticles, indicating that Pt is easy to agglomerate on the surface of the basic g-C3N4 to form nanoparticles under this synthesis condition, while in the double spherical aberration transmission electron microscopy image of Example 1, Pt exists in the form of single atoms and is evenly distributed, indicating that the introduction of cyano groups helps the stable existence of single atoms. The reason may be that the negatively charged cyano group is more likely to adsorb the positively charged Pt. After photoreduction, Pt can be bonded to the cyano group in the form of a single atom, thereby obtaining a stable single-atom coordination structure.
[0102] Photoluminescence spectrum: Figure 4 As shown, compared with Comparative Examples 1 and 2, the peaks at ~435 nm of Comparative Example 3 containing a cyano group and Example 1 containing a Pt single atom and a cyano group are extremely weakened, indicating that the cyano group and the Pt single atom can significantly reduce the recombination efficiency of photogenerated carriers.
[0103] UV-visible absorption spectrum and Kubelka-Munk equation conversion diagram: According to Figure 5 From the UV-visible absorption spectrum in (a), it can be concluded that the absorption edges of Comparative Examples 1, 2, 3 and Example 1 are 468.5, 476.8, 468.5 and 459.8 nm respectively. It can be clearly seen from the figure that Example 1 has a higher visible light absorption capacity, indicating that the introduction of cyano groups and Pt single atoms can improve the utilization efficiency of visible light. After conversion by the Kubelka-Munk equation, we get Figure 5 As shown in the curve (b), the band gap values of comparative examples 1, 2, 3 and embodiment 1 are 2.63, 2.59, 2.63 and 2.68 eV respectively. After comparison, it is found that the band gap value of embodiment 1 is slightly increased, indicating that the material has stronger redox ability.
[0104] H2O2 cycling performance diagram of Pt single atom / cyanide modified g-C3N4 photocatalyst: According to Figure 6 The cyclic performance test shows that the Pt single atom / cyanide modified g-C3N4 material has good photocatalytic performance stability. With a cycle of 1 h, the H2O2 production is retained at 87.32% after 4 cycles, proving that the single atom has good structural stability under the stabilization of the cyanide group.
[0105] Examples 1, 2, 3 and 4 investigated the catalysts prepared by using different ratios of raw materials A and B, different solvent thermal treatment processes and calcination curves and their performance tests. The catalyst obtained in Example 1 had the highest H2O2 yield, which could reach 43.67 mmol h -1 g -1 , AQE can reach 15.86%, and the loading amount of Pt single atom reaches 1.489 wt%. This result shows that the Pt single atom / cyano-modified g-C3N4 material prepared by the present invention has excellent H2O2 yield compared with similar materials, and the light energy utilization efficiency is significantly improved. The reason why this structure achieves excellent photocatalytic performance is that the cyano group stably connected to the g-C3N4 molecular structure serves as the loading site of Pt single atom, which effectively improves the loading amount and stability of single atom.
[0106] By comparing Example 1 and Example 2, the main reason for the performance difference is the content of cyano group and the bonding mode with g-C3N4, which in turn will cause the difference in the loading amount of Pt single atom. Too little cyano group will lead to too few loading sites of Pt single atom, and too much will lead to the destruction of g-C3N4 structure; the temperature and time of solvent thermal reaction affect the bonding stability of cyano group and g-C3N4; calcination temperature and time affect the degree of polycondensation reaction.
[0107] By comparing Example 1 and Example 3, the reason for the performance difference lies in the amount of Pt precursor added and [PtCl6] 2- Adsorption capacity in different solution environments. Too little addition of Pt precursor will result in low loading of Pt single atoms, while too much will easily lead to agglomeration during the photoreduction process; alkaline pH of the solution is more conducive to [PtCl6] 2- adsorption.
[0108] By comparing Example 1 and Example 4, the reason for the performance difference lies in the influence of light intensity and time on Pt reduction kinetics. If the light intensity is low and the light time is short, sufficient electrons cannot be stimulated to participate in the reduction reaction of Pt ions. If the light intensity is high and the light time is long, Pt will agglomerate, reducing the number of active sites involved in photocatalysis.
[0109] The above results compare and illustrate factors such as the ratio of cyanide adjuster, solvent thermal temperature and time, amount of Pt precursor added, solution pH, light intensity and time. The final catalyst performance and Pt loading are closely related to the above factors, and it is necessary to comprehensively adjust various parameters to obtain the optimal catalyst.
[0110] The above results indicate that the Pt single atom / cyanide-modified g-C3N4 catalyst obtained in the present invention has excellent catalytic activity and light energy utilization efficiency, and the Pt single atom is stable and not easy to agglomerate, and has broad application prospects in the degradation of water pollutants and new solar fuels.
[0111] The above is a description of the specific implementation methods of the present invention. However, the present invention is not limited to the above implementation methods. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Pt single atom / cyano modified g-C3N4 material, characterized in that: The solution containing raw material A and raw material B is subjected to solvent thermal treatment, followed by calcination to obtain a cyano-modified g-C3N4 material; the cyano-modified g-C3N4 material and the Pt source are then liquid-phase aged, frozen, and then photoreduced under a light intensity of 100-500 mW to obtain the Pt single atom / cyano-modified g-C3N4 material; The raw material A comprises at least one of Formula 1 and Formula 2; Formula 1; Formula 2; The chemical formula of the raw material B is MCl, wherein M is at least one of Na and K.
2. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to claim 1, characterized in that: The weight ratio of the raw material A to the raw material B is 1:1-5.
3. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to claim 1, characterized in that: The solvent in the solution includes water; wherein the concentration of raw material A is 20-50 g / L.
4. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to claim 1, characterized in that: The solvent thermal temperature is 100~180 ℃; the insulation time at the solvent thermal temperature is 1~8 h.
5. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to claim 1, characterized in that: The calcination temperature is 450~650 ℃; the holding time at the calcination temperature is 2~8 h.
6. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to claim 1, characterized in that: The Pt source is 10 wt% to 50 wt% of cyano-modified g-C3N4 material.
7. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to claim 1, characterized in that: The pH of the initial solution of liquid phase aging is controlled to be 5-10.
8. The method for preparing the Pt single atom / cyano modified g-C3N4 material according to any one of claims 1 to 7, characterized in that: The light intensity of photoreduction is 250~350 mW; the time of photoreduction is 2~15 min.
9. A Pt single atom / cyano group modified g-C3N4 material obtained by the preparation method according to any one of claims 1 to 8; characterized in that: It includes cyano-modified g-C3N4 material and single-atom Pt particles dispersed on the surface of the material, and the single-atom Pt particles and the cyano-modified g-C3N4 material have chemical bonding.
10. An application of a Pt single atom / cyano modified g-C3N4 material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It is used as a catalyst for photocatalytic production of H2O2.
Citation Information
Patent Citations
Surface cyano-modified carbon nitride nanotube photocatalyst and preparation method thereof
CN111715260A
KR20220158971A